Work-family conflict and psychological contract as predictors of work engagement: The mediating role of psychological well-being among married female employees - Ira Mulyana; Retno Dwiyanti; Mohd Nazri Abdul Rahman; Mahdi Anbari; Endah Silawati (Proyeksi, 2026)
This study aims to examine the relationship between work–family conflict and the psychological contract on work engagement, with psychological well-being as a mediating variable, among married female employees at a Regional General Hospital (RSUD). The research approach used is quantitative with an explanatory research design. The study participants consisted of 201 married female employees selected through random sampling. Data collection was conducted using four standardized psychological instruments measuring work–family conflict, psychological contract, psychological well-being, and work engagement. Data analysis was performed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method via SmartPLS software version 4. The results indicate that work–family conflict does not have a direct and significant effect on work engagement but does have a significant effect on psychological well-being. On the other hand, the psychological contract was found to have a positive and significant effect on both psychological well-being and work engagement. Furthermore, psychological well-being has a significant positive effect on work engagement and acts as a significant mediator in the relationship between work– family conflict and work engagement, as well as between the psychological contract and work engagement. These findings confirm that psychological well-being is an essential psychological mechanism in explaining work engagement among married female employees working in the healthcare sector.